2016
DOI: 10.3109/00016489.2016.1157266
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pneumolabyrinth after temporal bone trauma using computed tomography

Abstract: Only six patients (7% of those with OCD fractures or 1.5% of those with temporal bone fracture) were found to have pneumolabyrinth. Locations of the pneumolabyrinth were in the vestibule in all six cases and three of them showed air densities both in the cochlea and semicircular canal. The size of the air density in the vestibule was 5.38 ± 4.56 mm(2) at the axial view and 6.57 ± 5.67 mm(2) at the coronal view. The mean minimal Hounsfield unit (HU) of air density area in the vestibule was -968.1 ± 22.94 at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Previous studies on middle ear trauma or temporal bone fracture suggested that the location of pneumolabyrinth may serve as a prognostic factor for the recovery of inner ear dysfunction (6,21). In patients with middle ear trauma or temporal bone fracture, pneumolabyrinth was usually found in the vestibule adjacent to the oval window, because air entered the inner ear from the middle ear or mastoid cavity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on middle ear trauma or temporal bone fracture suggested that the location of pneumolabyrinth may serve as a prognostic factor for the recovery of inner ear dysfunction (6,21). In patients with middle ear trauma or temporal bone fracture, pneumolabyrinth was usually found in the vestibule adjacent to the oval window, because air entered the inner ear from the middle ear or mastoid cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pneumolabyrinth may vary according to the time interval between insult onset and imaging evaluation. A 10-year cohort study of patients with temporal bone fracture reported that pneumolabyrinth was observed in 1.5% of all temporal bone fractures diagnosed using TBCT regardless of the time at which imaging was performed after the trauma (6). In another study on temporal bone trauma, 8% of patients with temporal bone fracture who visited the emergency room showed pneumolabyrinth on TBCT performed on the day of the visit (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of air inside the labyrinth also called pneumolabyrinth, is a rare and abnormal finding which can be the result of communication between the middle ear spaces and the inner ear. The most common etiologies are trauma and iatrogenic manipulations around the oval window [4,[6][7][8][9][10]. Traumatic pneumolabyrinth can occur in 7.1-48.4% of OCD fractures but is not present in the cases of OCS fractures, thus it can be an indirect marker of OC damage [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of occurrence of pneumolabyrinth is seldom in comparison to other sequelae of temporal bone trauma. In a series by Choi et al the incidence of pneumolabyrinth was 8% among the trauma cases with temporal bone fracture while in another series by Choi et al it was 1.5% [2,3]. The various causes other than temporal bone fracture causing pneumolabyrinth are rupture of round window due to an impulsive force, perilymphatic fistula, displacement of stapes prosthesis into vestibule, congenital malformations, fracture or dislocation or subluxation of stapes and cochleostomy with cochlear implant within [4][5][6][7][8][9][10].…”
Section: Global Journal Of Otolaryngology Discussionmentioning
confidence: 99%